Pain management in osteoarthritis – aceclofenac as one of the therapeutic options - Okopień, Bogusław (Lekarz POZ, 2019)
Aceclofenac belongs to the group of nonsteroidal anti-inflammatory drugs (NSAIDs). Its mechanism of action relies on preferential cyclooxigenase-2 (COX-2) inhibition. As a result of this mechanism of action it is highly effective in the reduction of pain associated with spondyloarthrosis, rheumatoid arthritis, and ankylosing spondylitis. The high clinical efficacy of aceclofenac is accompanied by a preferential safety profile with reduced gastrointestinal side effects. The unique feature of aceclofenac is its pleiotropic anti-inflammatory potential, which extends beyond COX inhibition and leads to reduction in levels of proinflammatory cytokines (e.g. interleukin 1). Importantly, aceclofenac as a member of NSAIDs can be used as a part of the analgesic ladder, which is a World Health Organisation (WHO) campaign to fight chronic pain.